Towards sustainable consumption: The role of knowledge, environment, and promotion for the millennial generation - Muhyidin, Ayi; Istimal, Imal; Sutar, Sutar; Maswanto, Maswanto (Universitas Negeri Surabaya, Indonesia, 2024)
The millennial generation plays a crucial role in consumer decision-making and has great potential in driving the transformation towards more sustainable consumption patterns. This research investigates how environmental knowledge, environmental influences, and promotion of sustainable consumption affect the intentions and behaviours of sustainable consumption among the millennial generation. To test this framework, this study employed a quantitative research approach by conducting an online survey to collect data from millennial respondents, with a total sample of 155 individuals. This study used Structural Equation Modelling to test the proposed hypotheses. The findings of this study indicate that the level of environmental knowledge, environmental influences, and the effectiveness of promotion of sustainable consumption have a significant impact on consumer's intention to adopt sustainable consumption behaviours, which in turn are related to actual actions in sustainable consumption. The results of this research provide in-depth insights into how elements such as knowledge, social environment, and promotion can act as drivers or barriers for the millennial generation in adopting more sustainable consumption patterns. The implications of these findings have great potential in shaping more effective strategies and campaigns to promote sustainable consumption behaviours among the millennial generation while also increasing awareness of pressing environmental issues.